Aktywność inwestycyjna rolników w podregionie bydgoskim - Mańko, Stanisław; Sass, Roman; Sobczyński, Tadeusz (Investment Activity of Farmers in the Subregion Bydgoszcz, 2006)
The investment activity of farmers in subregion Bydgoszcz, which is estimated by the interest in credits in 1999-2005, was strongly diverse. There was no dependence between a number of opinions concerning applications for preferential credits and an area of farms, self-evaluation of ability to development and a number of people with higher education working on farms. It was found covariability of interest in investment credits and quality of agricultural production space.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 72-79